96.5k views
0 votes
3xsquared +13x-10

HELPP PLEASE

User Rayjax
by
5.0k points

1 Answer

6 votes

Answer:

(x + 5)(3x - 2)

Explanation:

Assuming you require the expression factorised.

3x² + 13x - 10

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 3 × - 10 = - 30 and sum = + 13

The factors are + 15 and - 2

Use these factors to split the x- term

3x² + 15x - 2x - 10 ( factor the first/second and third/fourth terms )

= 3x(x + 5) - 2(x + 5) ← factor out (x + 5) from each term

= (x + 5)(3x - 2) ← in factored form

User Tpdance
by
5.9k points